Caregiver Burden, Psychological Well-Being and Coping Strategies of Parents Having Children with Thalassemia - Naveed Alam Khan; Dr. Abdur Rashid; Misbah Ullah; Kainat Javed (Research Journal of Psychology, 2025)
Thalassemia is a chronic disease caused by a genetic defect that interferes with a child's normal physiological functioning and affects the physica1, emotional, and cognitive wel1-being of individuals and their families. Children with thalassemia have to go to the hospital on a frequent basis for b1ood transfusions. Parents are burdened psychologically because of the expenses, stress, and fear of loss. A total of 100 subjects were se1ected using the convenient samp1ing technique. Data was analyzed by using descriptive statistics to find out the frequencies and percentages of the basic variables. Among the parents of thalassemia children residing in Khyber Pakhtunkhwa, the current study was conducted to determine the relationship between the caregiver burden, coping mechanisms, and psychological well-being of parents of thalassemic children. The Zarit burden interview scale, Jalowiec Coping Scale A, Jalowiec Coping Scale B, and The Warwick-Edinburgh Mental Well Being Scale (WEMWBS) was used. A1l the scales demonstrated good re1iability for the current population. The findings suggest that monthly income was significantly negatively correlated with the caregiver burden of parents of thalassemic children in Khyber Pakhtunkhwa. A significant negative correlation between the level of care giver burden of thalassemic children and Psychological well –being of parents of thalassemic children was also found.